CORRELATION OF SHEAR WAVE VELOCITY WITH SPT-N FOR A TOWER- BUILDING SITE AT ERBIL CITY - HASAN, AHMED MOHAMMED; MAWLOOD, YOUSIF ISMAEL; AHMED, AZAD A.; IBRAHIM, HAWKAR HASHIM (Journal of Duhok University, 2021)
Measurement of shear wave velocity (Vs) plays a crucial role in ground movements around geotechnical structures such as building foundations in the urban area and tunnels. Basically, measuring Vs often requires when seismic properties of soils are essential to be calculated, such as elastic shear modulus. Multichannel analysis of surface wave (MASW) is one of the seismic methods which employs surface waves to measure Vs. It is often not available along with site investigation due to high cost, complicated technical analysis, noise pollution, space constraints, etc. Hence, it is essential to predict Vs through correlating it to other soil parameters such as standard penetration test blows count (SPT-N). Therefore, the main focus in the current study was to correlate between Vs and SPT-N using an empirical equation likely applied for clay soils. A complementary subsoil investigation was performed of a tower- building at Erbil City, including SPT-N values for three boreholes and their corresponding MASW measurements. These data were, in turn, used to estimate Vs from corrected SPT-N. The currently proposed equation compared with the existing ones in the literature. The comparison shows that the proposed equation predicts the values of Vs as good as those available in the literature for both of the datasets in the current and the previous studies.